Innovations in Electronics and Communication Engineering Proceedings of the 6th ICIECE 2017 - Saini, H. S.; Singh, Ravi Kishore; Patel, Vishal M.; Santhi, K.; Ranganayakulu, S.V (Lecture Notes in Networks and Systems, 2019)
The book is a collection of best selected research papers presented at 6th International Conference on Innovations in Electronics and Communication Engineering at Guru Nanak Institutions Hyderabad, India. The book presents works from researchers, technocrats and experts about latest technologies in electronic and communication engineering. The book covers various streams of communication engineering like signal processing, VLSI design, embedded systems, wireless communications, and electronics and communications in general. The authors have discussed the latest cutting edge technology and the volume will serve as a reference for young researchers.